Ocorrência de lesões perioperatórias por posicionamento e fatores associados - PEIXOTO, Camila de Assunção (2017)
The occurrence of perioperative positioning-related injury is one of the most frequent adverse events in the surgical patient, and it has a multifactorial etiology. This study was intended to assess the risk of perioperative positioning-related injuries, according to the Risk Assessment Scale for the Development of Injuries due to Surgical Positioning (ELPO), and the associated sociodemographic, clinical and surgical-anesthetic factors. This is an observational, longitudinal and prospective study, with a quantitative approach, which was performed at the surgical center of a teaching hospital in the state of Minas Gerais, Brazil. This study was attended by adult and elderly patients, males and females, submitted to elective surgery, reaching a total of 278 (n) patients. In order to collect data, we used an instrument encompassing sociodemographic and clinical variables and variables related to anestheticsurgical procedures, besides ELPO. We used descriptive statistics for the categorical variables; and for the descriptive measures of centrality and variability, we used quantitative variables. In order to associate the variables on color, gender, age, BMI, hypothermia, hemoglobin and ELPO with the occurrence of perioperative positioning-related injuries, we used logistic regression analysis. The significance level considered was 5%. This research was approved by the Research Ethics Committee of the Federal University of Triângulo Mineiro (UFTM), under Opinion nº 1,916,567. It was noted that most patients were females, 175 (62.9%); white, 162 (58.3%); adults, 203 (73%); and had some comorbiditie, 140 (50.4%), with an emphasis on arterial hypertension, 48 (17.3%), and normal hemoglobin, 209 (75.2%). Of the assessed patients, 101 (36.3%) were eutrophic. As for the variables related to the surgical-anesthetic procedure, 77 (27.7%) patients were submitted to digestive system surgeries and 158 (56.8%) were classified as ASA II. Of the surveyed surgeries, 103 (37.1%) lasted from 1 to 2 hours. Regional anesthesia, 119 (42.8%), and Trendelenburg position, 120 (43.2%), were the most frequent. The most commonly used support surface was the standard operating-table of foam with cushions made from cotton field, 251 (90.3%); and electrocautery was used in most surgeries, 243 (87.4%), although it was noted the occurrence of 1 (0.4%) burn. Most patients had hypothermia, 229 (82.4%). As for the risk for development of perioperative positioning-related injury, 157 (56.5%) of the patients showed a higher risk and 214 (77%) had pressure-induced skin lesions. None of the patients had focalalopecia. Regarding the association of sociodemographic and clinical factors, hypothermia and the ELPO risk with the occurrence of perioperative positioning-related injuries, only the color on variable (p<0.001) was considered as a predictor for the occurrence of perioperative positioning-related injury. Nevertheless, even though it was not statistically significant, most injuries took place in female patients, adults, with altered BMI, with hypothermia, with normal hemoglobin and with ELPO ≥ 20. Based on the foregoing, we can highlight the importance of risk identification, occurrence of perioperative positioning-related injuries and associated factors with a view to developing strategies that help in the prevention of complications in clinical practice or in the solution of these complications in a suitable period.